Antibacterial activity of water and ethanol extract of Allium sativum, Curcuma mangga, and Acorus calamus combination - Bayyinatul Muchtaromah; Mujahidin Ahmad; Romaidi Romaidi; Lina Ainun Nazilah; Nayla Alin Naja (The East Java Biological Society, 2018)
Madura has been known as an Indonesian tribe that usually used many recipes of traditional medicine in their daily life. One of the medicinal herbs to increase female fertility is the herbal